Cidade, Terra e Jogo Social: Apropriação e uso do Patrimônio Fundiário Natalense e seu impacto nas redes de poder locais (1903-1929) - Siqueira, Gabriela Fernandes de (2019)
The objective of this work is to investigate the process of appropriation and use of land patrimony of Natal associating it with the work of the local power networks in the early twentieth century. It was found the existence of a complex system of a proprietary culture with its own logic, which involved other points, such as the reciprocity relations to strengthen the networks that dominated the power and that reproduced in the urban landscape and in the occupation of the land these relationships marks. Governors and officials of the Intendência [Stewardship] used their privileged positions to benefit themselves from the policy of granting municipal lands, extanting lots of lotments, paying inexpressive annual land taxes, alienating lands for amounts not significant from the point of view of economic capital, strengthening their ties and setting a personal land market that involved the transaction of different types of capital. In order to investigate how the land market worked, it was fundamental to understand how these networks ascended to power and how they created a discourse of transformation of the city, participating in a social game that aimed to strengthen the influential groups to the detriment of public patrimony. There is a process marked by the ambiguity of liberal forms ligament with a patrimonialist and conservative political and administrative structure. There were used as sources periodicals, mainly A Republica and Diario do Natal, state laws and decrees, messages of governors, intendants reports, municipal resolutions, land solicitations, settlement letters, judicial processes, biographical dictionaries and memory books.